iMordecai [videorecording (DVD)] - Samel, Marvin; Gaines, Rudy; Heyman, Dahlia; Hirsch, Judd; Kane, Carol, 1952-; Astin, Sean; Hale, Azia Dinea (Kino Lorber, 2023)
When Mordecai, a Holocaust survivor, is given a new iPhone, an unexpected series of events upends his world. A heartwarming Miami-set comedy based on a true story.